Synergistic Antitumoral Effect of Epigenetic Inhibitors and Gemcitabine in Pancreatic Cancer Cells - Immacolata Maietta; Amparo Martínez-Pérez; Rosana Álvarez; Ángel R. De Lera; África González-Fernández; Rosana Simón-Vázquez (Pharmaceuticals, 2022)
Epigenetic modifications could drive some of the molecular events implicated in proliferation, drug resistance and metastasis of pancreatic ductal adenocarcinoma (PDAC). Thus, epigenetic enzyme inhibitors could be the key to revert those events and transform PDAC into a drug-sensitive tumor. We performed a systematic study with five different epigenetic enzyme inhibitors (1, UVI5008, MS275, psammaplin A, and BIX01294) targeting either Histone Deacetylase (HDAC) 1 or 1/4, DNA methyltransferase 3a (DNMT3a), Euchromatic histone lysine methyltransferase 2 (EHMT2), or Sirtuin 1 (SIRT1), as well as one drug that restores the p53 function (P53R3), in three different human PDAC cell lines (SKPC-1, MIA PaCa-2, and BxPC-3) using 2D and 3D cell cultures. The synergistic effect of these antitumoral drugs with gemcitabine was tested and the most efficient combinations were characterized by RNA-seq. The inhibition of HDAC1/4 (MS275), HDAC1/4/SIRT1/DNMT3a (UVI5008) or EHMT2 (BIX01294) induced a significant reduction on the cell viability, even in gemcitabine-resistance cells. The combination of UVI5008 or MS275 with gemcitabine induced a synergistic effect at low concentration and the RNA-Seq analysis revealed some synergy candidate genes as potential biomarkers. Reverting aberrant epigenetic modifications in combination with gemcitabine offers an alternative treatment for PDAC patients, with an important reduction of the therapeutic dose.